Capitalist reconfiguration. The rise of China and the position of South America in the world economy - Lauxmann, Carolina T.; Trevignani, Manuel F. (FLACSO - Sede Ecuador, 2023)
The capitalist system in its historical evolution has created different institutional and spatiotemporal fixes to guarantee its sustainability. The contemporary fix, which enabled the reproduction of capital through global production chains, generated unprecedented changes. For the first time, the dynamic center of accumulation is located in a peripheral space: East Asia, led by China since the beginning of the century. This article, based on bibliographic and statistical data, analyzes the characteristics of the aforementioned fix and the specificities of the East Asian countries that allowed them to increase capital accumulation and improve their position in the global economy. The implications of the rise of this region for the capitalist system and for South America are also examined. It is concluded that South American countries have not been able to develop after their integration into globalized production; they reinforced their specialization in low-value and low-complexity activities. The rise of East Asia seems to intensify this dynamic. However, while the new scenario generates global disputes that reposition the accumulation in national and macro-regional spaces, it opens opportunities to qualify the international position of the South American region through its productive integration.